2015
DOI: 10.4314/ejesm.v8i5.10
|View full text |Cite
|
Sign up to set email alerts
|

Urban housing quality and its health implications in Nigeria: an example of Lokoja, Kogi State, Nigeria

Abstract: Developing countries are faced with qualitative and quantitative housing inadequacies. Living conditions in many urban areas are squalid and pose serious health challenges on the inhabitants. This study examines the housing quality and its health implications in Lokoja metropolis. Both primary and secondary data were employed. A structured questionnaire was designed. An average of forty questionnaires was distributed across each of the three residential areas identified in the city to elicit information about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Regarding the availability of sanitary latrines, 6% of residences had no sanitary toilets (see Figure 7), and this has serious implications for open defecation with its attendant environmental and health consequences, especially the spread of faeco-oral infections. A comparable but much higher result was also well documented by Adetunji and Isah [24], who found that 82.8% of those surveyed have a toilet at their residences in a recently published study on quality of housing and the implications in Lokoja. Approximately 17.2 percent of the remaining respondents claimed that toilet facilities were inaccessible.…”
Section: Prevalent Health Conditionssupporting
confidence: 73%
See 1 more Smart Citation
“…Regarding the availability of sanitary latrines, 6% of residences had no sanitary toilets (see Figure 7), and this has serious implications for open defecation with its attendant environmental and health consequences, especially the spread of faeco-oral infections. A comparable but much higher result was also well documented by Adetunji and Isah [24], who found that 82.8% of those surveyed have a toilet at their residences in a recently published study on quality of housing and the implications in Lokoja. Approximately 17.2 percent of the remaining respondents claimed that toilet facilities were inaccessible.…”
Section: Prevalent Health Conditionssupporting
confidence: 73%
“…In agreement with the current outcome, Udoh and Uyanga [7] reported that 78% of households in rural Akwa Ibom fell quite below the minimum requirement for water access. Similarly, a recent published work in Lokoja indicated that tap water was available to 59.2% of the city's residents [24]. The paper went further to show that 11.2% of the residents in Lokoja rely on well water for their domestic uses, which is subject to contamination if the sanitary conditions are not met.…”
Section: Prevalent Health Conditionsmentioning
confidence: 86%
“…For instance, over the past few decades, the city of Lokoja (administrative capital of Kogi State at the confluence of the Niger and Benue rivers) has experienced high and rapid rates of urbanisation, characterised by unplanned city expansion along with the suburbs and periphery (Alabi, 2009;Ukoje, 2016). Studies on the urbanisation and expansion feature of the city report that Lokoja is currently facing significant challenges in its quality of life and the range of opportunities it can offer its residents (Fatiregun, Mofolorunsho & Osagbemi, 2009;Adetunji & Isah, 2015). Overcrowding, slum development, flooding, noise pollution, poor air quality, traffic congestion, poor waste-management systems, and industrial emissions are the current liveability challenges associated with Lokoja.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a lack of research on the liveability experience in informal spaces such as Kabawa community of Lokoja, because informal spaces, as sub-city fragments of urban space, remain excluded in scientific investigations (Samper et al, 2020: 1;Maemeko, Mukwambo & Nkengbeza, 2021: 39). Kabawa is one of the informal districts in Lokoja which exhibits a high degree of slum characteristics, including overcrowding, poor and inadequate sanitation facilities, flooding, noise pollution, poor air quality, and unhealthy waste-management systems (Fatiregun et al, 2009;Adetunji & Isah, 2015;Ukoje, 2016).…”
Section: Introductionmentioning
confidence: 99%